Prevalence of human T‐lymphotropic virus type 1 carriers among pregnant women in Hokkaido, Japan. (August 2014) - Yamada, Takahiro; Togashi, Takehiro; Tsutsumi, Hiroyuki; Imamura, Masahiro; Okubo, Hitoshi; Okabe, Mihiro; Takamuro, Noriko; Tashiro, Kunio; Yano, Koichi; Yamamoto, Nagafumi; Hirakawa, Yukiko; Minakami, Hisanori
ABSTRACT As there is a risk of MTCT of HTLV‐1, the HSGP HTLV‐1 MTCT was organized in 2011. To determine how many pregnant women are infected with HTLV‐1 in Hokkaido, which is the northernmost and the second largest island in Japan with a population of 5 467 000 and 39 392 newborns in 2011, the HSGP HTLV‐1 MTCT asked all facilities that may care for pregnant women in Hokkaido in July 2013 to provide information on the number of pregnant women who underwent screening for anti‐HTLV‐1 antibody using particle agglutination or chemiluminescent enzyme immunoassay, and the numbers of those with positive, equivocal, and negative test results in the screening and confirmation tests using western blotting or PCR methods in 2012, respectively. A total of 111 facilities participated in this study and provided information on 33 617 pregnant women who underwent screening in 2012, corresponding to approximately 85% of all pregnant women who gave birth in Hokkaido in 2012. Of 81 candidates for a confirmation test because of positive (n = 77) or equivocal (n = 4) results on screening, 63 (78%) underwent the confirmation test and, finally, 34 (0.1%) and 33 563 (99.8%) women were judged to be HTLV‐1 carriers and non‐carriers, respectively. It was concluded that the prevalence rate of HTLV‐1 carriers was low, one per 1000 pregnant women in Hokkaido. Approximately 40 infants are born yearly to mothers infected with HTLV‐1 in Hokkaido.